2016
DOI: 10.1007/s40484-016-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression analyses for single‐cell RNA‐Seq: old questions on new data

Abstract: Background: Single-cell RNA sequencing (scRNA-seq) is an emerging technology that enables high resolution detection of heterogeneities between cells. One important application of scRNA-seq data is to detect differential expression (DE) of genes. Currently, some researchers still use DE analysis methods developed for bulk RNA-Seq data on single-cell data, and some new methods for scRNA-seq data have also been developed. Bulk and single-cell RNA-seq data have different characteristics. A systematic evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…This leads 110 to reduced statistical power when attempting to identify differentially expressed marker genes. 111 Comparisons of various differential expression analysis methods for single-cell RNA-seq data have 112 shown that they yield different results both in terms of the number of detected DEG and consistency 113 of DEG's identity across the methods (Miao & Zhang, 2016). Performing pairwise differential 114 expression analysis to identify cell-type marker genes in heterogeneous single-cell RNA-seq data is 115 6 inefficient in terms of execution time and redundant use, especially when considering several cell-116 types in the heterogeneous cell population.…”
Section: Cell-type Identification 87mentioning
confidence: 99%
“…This leads 110 to reduced statistical power when attempting to identify differentially expressed marker genes. 111 Comparisons of various differential expression analysis methods for single-cell RNA-seq data have 112 shown that they yield different results both in terms of the number of detected DEG and consistency 113 of DEG's identity across the methods (Miao & Zhang, 2016). Performing pairwise differential 114 expression analysis to identify cell-type marker genes in heterogeneous single-cell RNA-seq data is 115 6 inefficient in terms of execution time and redundant use, especially when considering several cell-116 types in the heterogeneous cell population.…”
Section: Cell-type Identification 87mentioning
confidence: 99%
“…Differential expression (DE) analysis is to detect genes whose expression levels are significantly different between the compared groups of samples (11)(12)(13)(14)(15). It has been a key task in transcriptome study since the early days of microarrays.…”
Section: Introductionmentioning
confidence: 99%
“…It has been a key task in transcriptome study since the early days of microarrays. Traditional DE analysis methods for RNA-seq data were designed for bulk RNA sequencing (11,16,17), which needs millions of cells in one sample (6,18), and most of those DE analysis methods focus on the detection of DE genes by their mean expression levels (11,12,16,17,19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations